A Low Distortion Reversible Data Hiding Technique Using Improved PPVO Predictor. (2016) - Thomas, Neethu; Thomas, Shiney
Abstract: Reversible data hiding is a technique that embeds additional information into some distortion-unacceptable cover media, such as military images, in a reversible manner so that the original cover image can be restored after extraction of the hidden information. This work extends a recently proposed reversible data hiding (RDH) scheme of Qu et al. which is based on pixel-based pixel- value-ordering(PPVO) and prediction-error expansion. In Qu et al.'s method, each pixel is predicted using its sorted context pixels. In this work, the pixel neighborhood of each pixel is expanded to optimize the embedding performance in terms of capacity- distortion behavior. This can better exploit image redundancy; achieve superior embedding performance and low distortion. Thus, the proposed method is able to embed adequate data into a cover image with limited distortion. The superiority of this predictor is verified through extensive experimental results. The proposed method outperforms prior works in terms of PSNR. The PSNR of a modified image versus its original one is guaranteed to be above 57.0 dB.